Simcoe: Small-Town Ontario's Response to Extra-Community Change - March, Ruth Karen (My University, 1982)
This study examines the community power structure in the town of Simcoe. In the past ten years, the town of Simcoe has experienced extensive pressures on its social structure due to the extra-community influences of mass industrialization, urbanization and bureaucratization. Previous studies of community power structures reveal that when communities experience extra-community change the elite structure is factionalized. Community elites focus on conflict issues in an effort to gain access to the new resources of power or strengthen their current power positions. These factions are usually split in terms of localitecosmopolitan orientation or oldtimer-newcomer differences. This study finds that the Simcoe respondents do not differ significantly in their extra-community orientation or their social characteristics. Rather, it is the elite's social network ties that determines the faction to which he/she belongs and the way in which he/she can be seen to support an issue.
Keywords: Sociology; Sociology